Diabetes and oral health: A comparative cross-sectional analysis of DMFT index among diabetic, pre-diabetic, and non-diabetic adults - Mohammad Samami; Amir Valaei-Barhagh; Farahnaz Joukar; Soheil Hassanipour; Maryam Rabiei; Arman Habibi; Mohammad Reza Naghipour; Fariborz Mansour-Ghanaei (PLoS ONE, 2025)
Objective The objective of this study was to compare the DMFT index (decayed, missing, and filled teeth) between diabetic, pre-diabetic, and non-diabetic subjects and to determine whether sociodemographic (including age, education, or socioeconomic status) or health-related factors (such as BMI, smoking, or physical activity) were associated with DMFT levels in people with diabetes. Methods This study is cross-sectional and part of the PERSIAN Guilan cohort study. Demographic information, body mass index (BMI), cigarettes and hookah, alcohol and drug use, co-morbidity diseases, socio-economic status (SES), and DMFT of all 35–70-year-olds were investigated. Classification of diabetes status was done based on the result of the FBS test or self-report of the participant, or the use of hypoglycemic drugs. Results Out of 10520 people who participated in the study, 2531 people had diabetes, 1837 people had pre-diabetes, and 6152 people were non-diabetics. The average DMFT in diabetic, pre-diabetic, and non-diabetic participants was 16.03, 14.63, and 13.94, respectively, and the differences in DMFT between the three groups were statistically significant (P < 0.05). The risk for higher DMFT was older patient age, lower educational status, lower BMI, less physical activity, smoking, alcohol consumption, and not brushing. However, drug use is considered a risk factor only for diabetics. Conclusion In all groups, higher DMFT risk factors included older age, lower education, reduced BMI, less physical activity, smoking, alcohol consumption, and inadequate teeth brushing. Notably, drug use is regarded as a risk factor exclusively among participants with diabetes.